Analogy and Historical Approaches to Undergraduate Electromagnetic Education - You, Kok Yeow (Journal of Engineering Education Transformations, 2019)
Electromagnetic is a challenging course for those who are taking an undergraduate program in electrical and electronics engineering. The content of the electromagnetic is mostly focuses on theoretical physics and mathematics . the scope of the electromagnetic is broad and need time to familiarize themselves with these mathematical symbols and expressions. Thus summarized Moreover, , teaching contents should be . Recently, numerous teaching approaches have been proposed to overcome the above-mentioned issues. Albeit that those proposed approaches are convincing, it is rather difficult for them to practice due to the limitation of learning time and large amount of students. In this paper, the analysis of learning difficulties and suggestions are presented in order to enhance the teaching and learning process within a short period of time. Different types of analogies teaching methods have been suggested; it enables students to imagine the operational phenomena of the electromagnetic. Brief historical and biographical background of electromagnetic are suggested to be introduced to the students during the teaching and learning process. The foundation of electromagnetic theory serves as an essential path which lead to many practical and fascinating areas of the electrical engineering, thus, a stable grasp of the foundation is necessary, as it will lessen the learning difficulties.